Evaluation of electrophoretic patterns of soluble proteins in salt stressed potato callus - Forooghian, Setareh (Horticultural Biotechnology Research, 2015)
Assessment of genetic diversity based on various markers plays a key role in crop breeding programs. In thisÂ study, protein patterns of callus, produced from three potato cultivar (Sante, Savalan, and Agria) and grown underÂ salinity stress were investigated. Potato seedlings were generated in vitro and then explants were collected andÂ transferred onto MS media containing 5 mg/l 2, 4-D, and 2 mg/l kinetin to callus induction. Callus was placedÂ onto new MS media containing 0, 25, 50, 75, and 100 mM NaCl. A 1-month-old callus was evaluated in termsÂ of protein patterns using vertical electrophoresis. The results indicated that potato cultivars are divided into twoÂ main groups. Sante cultivar grown under no salt stress was placed in one group, and Agria cultivar grown underÂ different concentrations of NaCl put in a separate group. According to the results, most of protein bands wereÂ appeared in 6.5-29 kDa regions. In general, Savalan cultivar produced more protein bands than Sante or Agria.